Interleukin-17 and Its Implication in the Regulation of Differentiation and Function of Hematopoietic and Mesenchymal Stem Cells - Slavko Mojsilović; Aleksandra Jauković; Juan F. Santibañez; Diana Bugarski (Hindawi Limited, 2015)
Adult stem cells have a great potential applicability in regenerative medicine and cell-based therapies. However, there are still many unresolved issues concerning their biology, and the influence of the local microenvironment on properties of stem cells has been increasingly recognized. Interleukin (IL-) 17, as a cytokine implicated in many physiological and pathological processes, should be taken into consideration as a part of a regulatory network governing tissue-associated stem cells' fate. This review is focusing on the published data on the effects of IL-17 on the properties and function of hematopoietic and mesenchymal stem cells and trying to discuss that IL-17 achieves many of its roles by acting on adult stem cells.